Facile hydrothermal deposition of octahedral-shaped Cu2O crystallites on bamboo veneer for efficient degradation of organic aqueous solution. (March 2021) - Ma, Rumin; Chen, Yuhe; Yang, Yang; Wu, Zaixing; Bao, Yongjie; Li, Neng; Li, Jingpeng
Abstract: In this study, octahedral-shaped Cu2 O microcrystallites were fabricated on bamboo veneer via the facile hydrothermal method and characterized by scanning electron microscopy, energy dispersive spectrum, and X-ray diffraction. The results show that the octahedral-shaped Cu2 O microcrystallites with an average size of approximately 10–15 μm are self-assembled by small Cu2 O nanoparticles. After the immersion treatment by NaBH4, the catalytic efficiency of the prepared Cu2 O/bamboo composites can reach 97.9% within 6 min for the methylene blue degradation and 97.0% within 1 min for the methyl orange degradation. The catalytic mechanisms are discussed and attributed to the Cu2 O pseudomorphic conversion to Cu crystals for reduction and remarkable facet selective reduction by the (111) faceted Cu2 O micro-catalyst. Highlights: Cu2 O/bamboo composite was fabricated by facile low-temperature hydrothermal method. The composite has a high catalytic activity for the degradation of MB and MO. The octahedral-shaped Cu2 O has a remarkable (111) facet selective reduction. The Cu2 O octahedra was pseudomorphically converted to Cu by the reduction of NaBH4 .